2006
DOI: 10.1038/sj.gt.3302887
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin expression in host muscle following transplantation of muscle precursor cells modified with the phiC31 integrase

Abstract: Duchenne muscular dystrophy (DMD) is the most severe muscular dystrophy. It is caused by the absence of dystrophin in muscle fibers. The autologous transplantation of genetically corrected muscle precursor cells (MPCs) is a possible cure for DMD. A non-viral method of genetic modification was tested in this study. The co-transfection (nucleofection) of a phiC31 integrase and a transgene expressing plasmid in MPCs led to an increased stable expression in vitro. The stable expression of a small transgene (eGFP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 27 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…After transplanting one million corrected cells from these two groups into irradiated tibialis anterior muscles of mdx mice, immuno fl uorescence revealed that 3-6 weeks later, 250 muscle fi bers per crosssection were positive for the shortened fusion protein and fewer fi bers were positive for the full-length fusion. The restoration of the dystrophin complex was con fi rmed via co-localization of the dystrophin-associated proteins a -sarcoglycan and b -dystroglycan, which were found to be correctly localized at the membrane of the muscle fi bers (Quenneville et al 2007 ) . Additionally, human muscle precursor cells tranfected with a GFP-expressing donor plasmid and an integrase plasmid were observed to express GFP and grow for at least 35 days in vitro, following 1 week of selection.…”
Section: Therapeutic Uses Of F C31 Integrasementioning
confidence: 97%
See 3 more Smart Citations
“…After transplanting one million corrected cells from these two groups into irradiated tibialis anterior muscles of mdx mice, immuno fl uorescence revealed that 3-6 weeks later, 250 muscle fi bers per crosssection were positive for the shortened fusion protein and fewer fi bers were positive for the full-length fusion. The restoration of the dystrophin complex was con fi rmed via co-localization of the dystrophin-associated proteins a -sarcoglycan and b -dystroglycan, which were found to be correctly localized at the membrane of the muscle fi bers (Quenneville et al 2007 ) . Additionally, human muscle precursor cells tranfected with a GFP-expressing donor plasmid and an integrase plasmid were observed to express GFP and grow for at least 35 days in vitro, following 1 week of selection.…”
Section: Therapeutic Uses Of F C31 Integrasementioning
confidence: 97%
“…Additionally, human muscle precursor cells tranfected with a GFP-expressing donor plasmid and an integrase plasmid were observed to express GFP and grow for at least 35 days in vitro, following 1 week of selection. These cells were then transplanted into the tibialis anterior muscles of SCID mice, which can tolerate xenografts (Quenneville et al 2007 ) . After 1 month, the muscles were harvested, and the human cells were observed to have fused with mouse muscle fi bers and to express GFP.…”
Section: Therapeutic Uses Of F C31 Integrasementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several teams reported the ex-vivo correction of genetic human diseases in animal models of liver, skin diseases and Duchenne muscular dystrophy (Olivares et al 2002 ;Ortiz-Urda et al 2003 ;Quenneville et al 2007 ) . In mice, F C31-mediated integration of the gene encoding the human factor IX resulted in sustained expression of the therapeutic protein (Olivares et al 2002 ) .…”
Section: Site-speci Fi C Serine Recombinase F C31-based Vectorsmentioning
confidence: 98%